1999
DOI: 10.1139/cjpp-77-6-441
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of chilli pepper (<i>Capsicum annuum</i>) reduces salicylate bioavailability after oral aspirin administration in the rat

Abstract: The bioavailabilities of aspirin (acetylsalicylic acid) and of salicylic acid were studied in male Wistar rats after acute and chronic administration of a Capsicum annuum extract, containing 100 mg of capsaicin per gram. With a single administration of 100 mg/kg of the extract, aspirin blood levels remained unchanged, but salicylic acid bioavailability was reduced in 44% compared with control animals. With a single administration of 300 mg/kg of the extract, aspirin blood levels were undetectable while salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is an irritant for mammals, including humans, and produces a sensation of burning in any tissue with which it comes into contact. Cruz et al [208] reported that Capsicum annum reduces bioavailability of aspirin after oral administration in rats. Lopez et al [209] have shown that capsaicin has little or no impact on bioavailability of ciprofloxacin.…”
Section: Herbal Bioenhancersmentioning
confidence: 99%
“…It is an irritant for mammals, including humans, and produces a sensation of burning in any tissue with which it comes into contact. Cruz et al [208] reported that Capsicum annum reduces bioavailability of aspirin after oral administration in rats. Lopez et al [209] have shown that capsaicin has little or no impact on bioavailability of ciprofloxacin.…”
Section: Herbal Bioenhancersmentioning
confidence: 99%